2011
DOI: 10.1542/peds.2010-3225
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Palliative Care Patients: A Prospective Multicenter Cohort Study

Abstract: PPC teams currently serve a diverse cohort of children and young adults with life-threatening conditions. In contrast to the reported experience of adult-oriented palliative care teams, most PPC patients are alive for more than a year after initiating PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
315
4
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 385 publications
(357 citation statements)
references
References 14 publications
16
315
4
22
Order By: Relevance
“…For example, 71% of oncologists reported that patient death was particularly challenging when the family was unprepared for it, and 81% reported that it was hard for them when the patient who died was in pain. Substantial evidence indicates that the early integration of palliative care can prepare patients, their families, and the health care team for the end of life [35][36][37][38][39][40] , and in the process, it can also reduce miscommunication between patients, caregivers, and physicians 35,36,[41][42][43] . According to the National Consensus Project for Quality Palliative Care 44 , palliative care is defined as "patient and family-centered care that optimizes quality of life by anticipating, preventing, and treating suffering.…”
Section: "Bad Death"mentioning
confidence: 99%
“…For example, 71% of oncologists reported that patient death was particularly challenging when the family was unprepared for it, and 81% reported that it was hard for them when the patient who died was in pain. Substantial evidence indicates that the early integration of palliative care can prepare patients, their families, and the health care team for the end of life [35][36][37][38][39][40] , and in the process, it can also reduce miscommunication between patients, caregivers, and physicians 35,36,[41][42][43] . According to the National Consensus Project for Quality Palliative Care 44 , palliative care is defined as "patient and family-centered care that optimizes quality of life by anticipating, preventing, and treating suffering.…”
Section: "Bad Death"mentioning
confidence: 99%
“…Despite the variety of rare diagnoses comprising CCCs, this group of children frequently share a common set of underlying issues. 26 Broadly, these are categorized as neurologic issues (seizures, pain control, behavior/mood disorders), pulmonary issues (asthma, chronic lung disease, aspiration), gastrointestinal issues (gastrostomy tube, reflux, constipation), endocrine disturbances (adrenal insufficiency), and infectious issues (central line, catheter, or shunt infections). The likelihood of ADE visits related to vaccines was not significantly different between groups; this supports validity of our findings because most children should receive standard childhood vaccinations, which pose a low risk of ADEs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, especially for patients who do not suffer from cancer, there is often uncertainty regarding whether the outcome of the illness episode will, in fact, be death. 27 Awareness of such uncertainty is important for all members of the health care team as well as the family. For many competent adult patients who request aid in dying, the requests are often motivated by a desire to be in control of the circumstances of death.…”
Section: How Can One Tell the Difference Between Treating Suffering Amentioning
confidence: 99%